Factors affecting energy conservation behaviour of students in Malaysian universities - Low, Sheau Ting (2012)
This study focuses on promoting energy conservation using the behavioural approach. Globally, various energy issues such as the depletion of energy resources, degradation of the ecosystem, rise in energy prices, and increase in the world population, which lead to a higher energy demand, are causing a threat and leading to an unsustainable energy future. Among the immediate routes to minimize the adverse impacts of the energy threats and contribute to a sustainable energy future is the reduction of the energy consumption by promoting energy conservation behaviour. The scope of this study is Malaysian universities, which comprise thousands of building blocks equipped with massive facilities that consume a huge amount of energy. Three objectives to be achieved were established. The first objective is to propose key determinants and social marketing mix strategies to promote energy conservation behaviour. This is followed by the second objective of examining the causal relationship of the identified key determinants of energy conservation behaviour and the third objective of investigating the preferred combination of social marketing mix strategies to promote energy conservation behaviour. The first objective is achieved through the synthesis of theories and concepts in the literature review. For objective two and objective three, a questionnaire survey was conducted among students in five selected universities in Malaysia, which involved 2,000 respondents. The data collected for the second objective are analysed using structural equation modelling and the third objective is achieved using conjoint analysis. Three key determinants were found significant to predict energy conservation behaviour that are attitude, subjective norm, and perceived behavioural control. Choice-based conjoint analysis identified a mix of five social marketing strategies to promote energy conservation behaviour that are product, price, place, promotion, and post-purchase maintenance.